Iterative procedures combining cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for isolated peritoneal recurrence. (December 2014) - Vaira, Marco; Robella, Manuela; Mellano, Alfredo; Sottile, Antonino; De Simone, Michele
Abstract Purpose: The aim of this study was to analyse feasibility, morbidity and outcome of repeat complete cytoreductive surgery (CRS) plus hyperthermic intraperitoneal chemotherapy (HIPEC). CRS combined with HIPEC is becoming the gold standard treatment for resectable peritoneal carcinomatosis in highly selected patients. As yet treatment of isolated peritoneal recurrence with iterative CRS and HIPEC has not been thoroughly explored. Materials and methods: We selected 16 patients presenting isolated peritoneal recurrence who had undergone iterative CRS and HIPEC from a dataset of 322 CRS associated with HIPEC performed between 1996 and 2012. Results: Peritoneal carcinomatosis (PC) was due to colorectal and ovarian cancer, peritoneal mesothelioma and pseudomyxoma peritonei (PMP). Disease-free survival (DFS) was 13 months after the first procedure and 13.7 months after the second one. Overall morbidity rate was 43.7% (7/16) for all patients, with grade III–IV complications in three patients (18.7%). Conclusions: Iterative procedures combining cytoreductive surgery and HIPEC are feasible with acceptable morbidity and mortality rates in strictly selected patients. DFS following repeated CRS and HIPEC is comparable to that registered after the first procedure.